Hybrid line search and simulated annealing for production planning system in industrial engineering - Vasant, P. (IGI Global, 2014)
In this paper, the details on the optimization methods such as line search and simulated annealing for the local and global optimization have been highlighted. The hybrid line search and simulated annealing technique has been extensively explored in this research work. In this research the hybridization of line search and simulated annealing method provides satisfactory outcomes for the production planning problem in an uncertain environment. The major advantages and disadvantages of line search and simulated annealing also provided in this paper. The results for industrial production problem have been obtained successfully in the form of 2D and 3D plots. Copyright Â© 2014, IGI Global.